UUM's Islamic Business School receives 2016 GIFA award - Borneo Post, (Kuching) (Borneo Post (Kuching), 2016)
KUALA LUMPUR: Universiti Utara Malaysia's (UUM) Islamic Business School (IBS) received the 2016 Global Islamic Finance Award's Market Leadership award for Education in Islamic Banking & Finance.